Engaged at work? An employee engagement model in public relations. Issue 1 (4th March 2019) - Shen, Hongmei; Jiang, Hua
ABSTRACT: Engagement has emerged as an important concept in public relations scholarship. Yet a theoretically informed model with a clear and coherent explication of the construct is still lacking. By situating our study in the internal organizational context, we provided an updated conceptualization and operationalization of employee engagement, proposing a strategy-engagement-behavior three-step employee engagement model. Results from an employee survey ( n = 568) supported our conceptual model, showing that organizational engagement strategies positively predicted employee engagement, which in turn accounted for employees' positive and negative messaging behavior, as well as their contextual performance behavior. After controlling for significant demographic variables such as gender, age, organizational size, number of subordinates, and level of management position, we identified a complete mediation effect of employee engagement in our two-step structural equation modeling analysis.